1992
DOI: 10.1192/bjp.160.3.398
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Suicide in Schizophrenic In-patients

Abstract: A retrospective analysis of the clinical records of 53 schizophrenic in-patients who committed suicide, and the same number of matched control subjects, was carried out using a larger set of demographic, psychosocial and clinical variables. Univariate analysis of the data indicated an early disturbed psychosocial adjustment, more severe mental illness, unsatisfactory social situation, and more frequent suicidal behaviour in the suicide group. Suicide in schizophrenic in-patients thus appears to be closely conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
53
0
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 10 publications
14
53
0
4
Order By: Relevance
“…Perhaps the most concrete, most readily recognized risk factor for suicide is the presence of previous attempts (5,16,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Greater lethality of attempts, and fewer provisions for being rescued are also indicative of strong fatalistic intentions (5).…”
Section: Consistently Supported Risk Factors Previous Attemptsmentioning
confidence: 98%
“…Perhaps the most concrete, most readily recognized risk factor for suicide is the presence of previous attempts (5,16,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Greater lethality of attempts, and fewer provisions for being rescued are also indicative of strong fatalistic intentions (5).…”
Section: Consistently Supported Risk Factors Previous Attemptsmentioning
confidence: 98%
“…Seven studies (17)(18)(19)(20)(21)(22)(23) have so far investigated completed suicides among groups of 15 or more suicide victims with DSM-III or DSM-III-R schizophrenia. In these studies young adult age, male sex, and mean illness duration under 10 years have characterized suicide victims with schizophrenia.…”
mentioning
confidence: 99%
“…A study by Farberow et al (1961) supports this hypothesis, finding that schizophrenia suicides tended to have more education than control patients. However, others (Modestin et al, 1992) have found that completed suicides with a prior diagnosis of schizophrenia were m ore likely to have an illness associated with early onse t and poor psycho-social adjustment.…”
Section: Pre-m Orbid Personalitymentioning
confidence: 97%
“…Previous attempts have been widely reported as indicating suicidal risk in schizophrenia (Schaffer et al, 1974;Modestin et al, 1992;Hu et al, 1991;Cheng et al, 1990) as is the case for suicide generally. It has been suggested that this is the clearest indicator of future risk.…”
Section: Previous Attem Ptsmentioning
confidence: 98%